Thermal Performance of the Atrium Building in Hot and Humid Climate - Aram, Reihaneh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The proper atrium design can be an optimum way for providing maximum users’ satisfaction and energy efficiency throughout different seasons. In a hot and humid climate, using a buffer zone as the atrium caused a thermal performance problem. One of the problematic issues can conclude as fluctuation in indoor conditions which is caused discomfort hours. This research investigates the thermal performance of the atrium building in a hot and humid climate based on different design parameters. Furthermore, this research deals with the ASHRAE (2018) - ISO 7730 - EN 25251 standards of energy performance and users’ thermal comfort for the atrium in single-floor, medium-rise, and high-rise office buildings. It applies different proportions of office and atrium volumes in finding the optimum design and assessing the different atrium window opening ratios, internal condition systems, and atrium orientations throughout a year. The EDSL Tas software was used for dynamic thermal simulations. The goal of this study to propose the optimum atrium and office volumes for buildings in a hot and humid climate based on thermal performance in the different seasons. The findings of this research illustrate that when the internal condition of the building is natural ventilation, the single-floor and medium-rise atrium buildings with an atrium proportion 1/2 of the office proportion with south-east (single-floor) and center (medium-rise) atrium placements had maximum occupants’ satisfaction (users’ comfort). However, when the internal condition of the building was mechanically conditioned (basic air-conditioning) and the atrium proportion was 1/3 and 1/4 of the office proportion, especially with the center (single-floor) and north-east (medium-rise) atrium placement, it had an acceptable internal comfort throughout the year. Furthermore, the high-rise atrium building with a natural internal condition and an atrium proportion 1/4 of the office proportion in the north-east placement, and the mechanically conditioned (basic air-conditioning) 1/3 atrium proportion of the office proportion in the center placement had more internal thermal comfort than other dynamic simulation scenarios during the year. Keywords: Atrium Volume, Atrium Orientation, Naturally Conditioned Building, Mechanically Conditioned Building, Hot and Humid Climate, EDSL Tas.

ÖZ: Atriyum tasarımı ile maksimum ısıl konfor ve enerji verimliliği yüksek olan, tüm mevsimlerde kullanılabilen sürdürülebilir bina tasarlayabiliriz. Bu tezin kapsamında ASHRAE (2018), ISO 7730, EN 25251 uluslararası standartları kullanılarak tek kat, orta ve yüksek katlı ofis binaları incelenmiştir. Optimum tasarım için farklı pencere açılış oranları, iç mekan koşulları, farklı atriyum yönledirmeleri ve farklı ofis-atriyum oranları yıl boyunca EDSL Tas yazılımı ile bulunması bu tezin amacıdır. Bu araştırmanın bulguları, doğal havalandırma kapsamında tek ve orta katlı ofis binasının yarı hacmi atriyum olduğunda ve güney-doğu yönü ile maksimum kullanıcı konforu sağlanabilmektedir. Mekanik havalandırma kullanıldığında ise 1/3 ile 1/4 atriyum ile ofis oranı ve merkezi atriyum-tek katlı bina, kuzey-doğu ile orta katlı bina olduğunda maksimum kullanıcı memnuniyeti sağlandığı görülmüştür. Ayrıca, doğal havalandırmalı yüksek katlı bina için ofis hacminin 1/4 oranında kuzey-doğu yönünde atriyum tasarımı ile 1/3 oranında mekanik havalandırmalı merkezi konumu olan atriyum tasarımı olduğunda her iki senaryoda yıl bazında tüm diğer simülasyonlar içerisinde en fazla ısıl konfor sağlamıştır. Anahtar Kelimeler: Atriyum Hacmi, Atriyum Oryantasyonu, Doğal Havalandırılmış Bina, Mekanik Havalandırılmış Bina, Sıcak ve Nemli Iklim, EDSL Tas.
Doctor of Philosophy in Architecture. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2020. Supervisor: Assoc. Prof. Dr. Zafer Alibaba
Keywords: Architecture; Renewable energy sources; Sustainable Buildings; Buildings--Thermal properties; Atrium Volume; Atrium Orientation; Naturally Conditioned Building; Mechanically Conditioned Building; Hot and Humid Climate; EDSL Tas